FAKTOR-FAKTOR YANG MEMENGARUHI KEBERLANJUTAN PERGURUAN TINGGI DI BANTEN - Muhammad Johan Widikusyanto; Join Satria (Universitas Serang Raya, 2015)
The conditions of competition between universities, encourage every college in Banten should be able to retain students and get new students every year. Lack of new students make a drawback college operating costs that eventually forced them to shut down the university. Thus, the organization of a college sustainability is largely determined their success in getting new students every year. Decision prospective college students in determining the choice is very important for the sustainability of any college in Banten. How do prospective students make decisions and what factors into consideration in their decision to become the information that must be .known every college to survive or even win the competition in the educational servicesindustry in Banten. Understanding how these factors work to influence students in making .a decision, expected to be able to increase the competitive ability of colleges in Banten.Survey research design used to obtain the data to be analyzed using a SEM with AMOS software assistance. The questionnaire distributed to 418 high school students both vocational public and private in Banten.The SEM estimation results indicate that Services, Cost, and the Reference Group effect on the decisions of prospective students in choosing a college to continue his studies. While the location has no effect on the decisions of prospective students. Reference Group possessed the greatest influence, followed by service products, and then the cost. Thus, the promotion should be directed at targets other than the market itself, but also especially in the reference group with positioning of superior educational services and the education costs affordable and systematically payments that help students finish their collegeeducation.